Newman's theory of health as expanding consciousness: an evolutionary concept analysis - Hongman Li; Ying Xiong; Zengjie Ye (BMC, 2024)
Abstract Background The health as expanding consciousness (HEC) theory posits that health and disease are interconnected components of a comprehensive process aimed at expanding consciousness. Aim The objective of this study is to introduce the concept, research status and applications of HEC and offer a comprehensive understanding of its various key components. Data sources Databases including EMBASE, PubMed, ScienceDirect, ProQuest, Wiley, Web of Science, Sinomed, China National Knowledge Infrastructure, Wanfang, and CQVIP, covering the period from 1986 to 2023. Method Employing Rodgers' evolutionary concept analysis approach, this study included and analysed 70 studies. Results The characteristics of HEC comprise aspects such as movement, time, space, energy, rhythm, and paradigm of health. The antecedents of HEC encompass disease, chaos, binding, centring, and choice point. Consequences associated with HEC include self-transcendence, unbinding, decentring, expanded consciousness, real freedom, pattern recognition, absolute consciousness, and death. Conclusion This study has identified substitute terms, related concepts, attributes, antecedents, consequences, and empirical references associated with HEC. The findings provide valuable information applicable across various domains of nursing, encompassing practice, education, research, and management.